Criação da base de dados e mapeamento conceitual para elaboração do tesauro da Literatura de Cordel - Albuquerque, Maria Elizabeth Baltar Carneiro de; Martins, Gracy Kelli; Santos, Raimunda Fernanda dos; Mota, Denysson Axel Ribeiro; Felipe, André Anderson Cavalcante; Gaudêncio, Sale Mário; Gonçalves, Eveline Filgueiras; França, Fabiana da Silva; Lunardelli, Rosane Suely Álvares; Serra, Lucélia Mara de Souza; Urtiga, Maria Eduarda Dantas Hardman (Revista Fontes Documentais, 2023)
93 This report describes the creation process of the Cordel Literature Database, whose leaflets were analyzed with the objective of identifying their themes and organizing their conceptual structure for the future elaboration of a thesaurus of the area. The leaflets available on the database are part of several collections and are authored by popular poets identified in previous research. Discursive Semantics (GREIMAS, 1976) was the method of linguistic and textual analysis used to identify the themes addressed in the cordel leaflets. The Thematic Classes for cordel leaflets, created by Albuquerque (2011), were the starting point of the analysis of the research corpus and they provided the opportunity to organize and demonstrate the semantic relationships between the themes and figures identified in the leaflets. As a result, 27 Thematic Classes were created, called Categories in this study, and each of these were broken down into Subcategories with their respective concepts, to assist in the thematic representation and facilitate the retrieval of the cordel leaflet. The study enabled the construction of a database in which 2,668 titles of cordel leaflets are organized, represented in a thematic way. The data collected and organized in this first phase will allow the elaboration of the ‘Thesaurus of Cordel Literature’, the next action to be carried out by the research.